The Gordon Memorial Lecture: novel approaches to controlling bacterial infections. Issue 5 (3rd September 2019) - Barrow, P.
ABSTRACT: 1. There is huge emphasis in veterinary and agricultural science in understanding the basics of processes and exploiting them for benefits to the economy and human and animal welfare. It is always valuable to be able to step back from existing or favourite hypotheses and paradigms to look at an area of work or problem and see whether a different approach might be productive particularly by drawing parallels with other sometimes unrelated problems. 2. This approach has been used to explore (i) the use of live, attenuated Salmonella vaccines to generate a new form of competitive exclusion, (ii) gene expression technology for the design of improved inactivated vaccines (iii) use of cytokine therapy to reduce persistent carriage by Salmonella, (iv) using bacteriophages to reduce carcass contamination by food-borne pathogens and reduce carriage of antibiotic resistance plasmids. 3. The potential for extending virus therapy to parasite infections is also discussed.